Assessment of Bio-social Aspect with Cholelithiasis Patients in Baghdad City - shanon, Abd Al-Kareem; tawfiq, Narmeen (Iraqi National Journal of Nursing Specialties, 2006)
Objective: To find out the relationship between the bio-social aspect with cholelithiasis patients and demographic characteristics in Baghdad city. Methodology: A purposive (non-probability) sample of (100) patients, from (20-70) years old, who were selected from patients who were admitted to hospital at preoperative stage, from Gastroenterology and Hepatology Hospital, Baghdad Teaching Hospital, Al-Yarmook Teaching Hospital, Al-Karama Teaching Hospital, Teaching Hospital. A descriptive study was carried out from 25th of June 2004 to the end of October 2004. An assessment form was constructed for the purpose of the study. Test-retest reliability was employed through computation of Pearson correlation coefficient. Content validity of the assessment form was determined through a panel of experts. Data were collected with interview technique. Data were analyzed through descriptive statistical approach (frequency and percentage) and inferential statistical approach (chi-square and correlation coefficient). Results: The study indicated that the mean of age was (52.6) year. The majority of them were females who fair; multiparty lived in urban, obesity, illiterate, low socio-economic status. The result of the study confirmed that the bio-social aspect had an effect on the incidence of cholelithiasis. Recommendations: The study recommended that the number of Gastroenterology and Hepatology Hospital should be increased in Iraq because; some of the patients come to Baghdad to treatment. Patients with positive family history for cholelithiasis must be educated and informed about [diet and fluid, which are related to gallstones, exercise, Regular follow-up include, (routine X-ray, ultra-sound general laboratory investigations), drugs use and side effect].